Academic stress and resilience in relation to academic performance in stomatology students - Kenia Betancourt Gamboa; Miriela Betancourt Valladares; Dianelys Busquets Carballo; Julio Antonio Guerra Menéndez; Mayelin Hernández Rodríguez; José Luis Cadenas Freixas (Edumecentro)
Background: in medical science careers, students are in interaction with various factors that represent sources of academic stress; therefore, their resilience capacity is essential to contribute to a successful academic performance. Objective: to determine the relationship between academic performance, resilience capacity and academic stress levels in second year students of Stomatology. Methods: a descriptive and transversal research was carried out in the Faculty of Stomatology of the University of Medical Sciences of Camagüey, between January and March 2023. Theoretical and empirical methods were used for the basis of the research and the collection of information. Wagnild's 14-item Resilience Scale (RS-14) and the SISCO Academic Stress Inventory were applied. Academic performance was provided by the teaching secretary, from the MS-19 model. The information was processed using the SPSS statistical program version 26.0 for Windows. Descriptive statistics included summary measures such as percentage, Chi-square of independence and Bartholomew's non-parametric Chi-square test. Results: it was found that there is a high number of students showing moderate stress levels and high resilience capacity; in general, academic performance was good. Conclusions: it was determined that there is a significant association between stress and academic performance, but not between resilience and academic performance.